A highly stable and versatile heterobifunctional fluoroalkylation reagent for preparation of fluorinated organic compounds. Issue 19 (25th April 2016) - Dai, Jingwen; Li, Zili; Wang, Taisheng; Bai, Ruke
Abstract : A highly stable heterobifunctional fluoroalkylation reagent, 1-azido-2-chloro-1, 1, 2-trifluoro-2-iodoethane (ACTI) has been prepared and investigated systematically. Abstract : A highly stable heterobifunctional fluoroalkylation reagent, 1-azido-2-chloro-1, 1, 2-trifluoro-2-iodoethane (ACTI) has been prepared in high yield for the first time by a new method. Moreover, the reactivity of both the azido group and the iodine atom of the reagent was systematically investigated and the results demonstrate that this compound is a very versatile and useful new fluoroalkylation reagent for preparation of fluorinated organic compounds.